Effect of covid-19 restrictions on nomophobia and smartphone addiction levels - Fidancı, İzzet and Aksoy, Hilal and Yengil Taci, Duygu and Ayhan Başer, Duygu and Cankurtaran, Mustafa (Journal of Dependence, 2021)
Objective: The aim of this study is to investigate the effect of the restrictions imposed due to the COVID-19 Pandemic on nomophobia and smartphone addiction levels. Method: People aged 18 and over who agreed to participate in the study and who have applied the "Nomophobia Scale" and the "Smartphone Addiction Scale" (SAS) within 1 year before the pandemic restrictions were included in the study by applying the same questionnaire during the period after the pandemic restrictions. Results: The number of participants was 100. A statistically significant difference was found between the prepandemic and post-pandemic nomophobia scores of the participants. While the mean nomophobia score was 74.2 before the pandemic, it was 76.2 after the pandemic. There was a statistically significant difference between the smartphone addiction scale scores of the participants before and after the pandemic. While the mean SAS score before the pandemic was 34.0, it increased to 36.7 after the pandemic. Conclusion: Behavioral changes are inevitable during the COVID-19 pandemic and the need for technology has increased. Therefore, necessary measures should be taken to prevent psychological disorders caused by the increase in technology-related addiction levels, and efforts should be made to reduce or control addiction levels.